PENGARUH PENAMBAHAN TEPUNG LABU KUNING TERHADAP SERAT PANGAN MUFFIN, KARAKTERISTIK FISIKOKIMIA DAN SENSORI - Rina Rismaya; Elvira Syamsir; Budi Nurtama (Jurnal Teknologi dan Industri Pangan, 2018)
Pumpkin is one of the high-fiber food sources which is abundant in Indonesia, but it is still widely un-derutilized. The use of pumpkin was expected to increase dietary fiber content in food product as well as to become one of food diversification alternatives. The purposes of this research were to evaluate the effect of addition of pumpkin flour into muffin formula on dietary fiber content, physicochemical and sensory cha-racteristics as well as to determine the best muffin developed. This research used Completely Randomized Design (CRD) which applied two factors namely, types of pumpkin flour (AP and AB) and the concentra-tions of pumpkin flour (25, 50, 75 and 100%). The study was repeated twice in three replication trials. The AP pumpkin was soaked in 0.10% sodium metabisulfite (Na2S2O5) solution at an initial temperature of 80°C, while AB pumpkin was soaked in a 0.10% Na2S2O5 solution at a room temperature (30°C). The re-sults showed that the increasing concentration levels of both pumpkin flour types decreased expansion volume, brightness, moisture content, and panelist acceptance towards the muffins. On the other hand, it increased bulk density, hardness, and dietary fiber content of the muffins. Based on sensory evaluation, the formulation comprising of 75:25 wheat flour to AB pumpkin ratio produced the best preferred muffin, because it was comparable to the control. Although the pumpkin muffin had lower acceptability than the control for all organoleptic parameters, it had a excellent value of dietary fiber. About one serving (ca 45 g) of 100% pumpkin muffin could meet the daily needs for Indonesian, at 29-31% per individual per day.